Amphiphilic [tpy-MII-tpy] metallotriangles: synthesis, characterisation and hierarchical ordering. Issue 1 (2nd January 2017) - Ludlow, James M.; Saunders, Mary Jane; Huang, Mingjun; Guo, Zaihong; Moorefield, Charles N.; Cheng, Stephen Z. D.; Wesdemiotis, Chrys; Newkome, George R.
Abstract: Long chain (C16 ) alkylated metallocycles are synthesised and characterised. Their ordered aggregation was studied via TEM to gauge to the effects of molecular topology, solvent, counterion and metal centre(s) on morphology and nanoscale structure. The results indicate that their amphiphilicity significantly enhanced their self-ordering characteristics relative to controls and enabled the formation of nanoscale structures. Similar ordering was observed for both labile and non-labile analogues with SAXD showing comparable d-spacing values, suggesting the presence of intramolecular π–π stacking. Effect of counterion and solvent was studied with the non-labile system. Nanotubular, ribbon, or sheet-like structures were afforded depending upon conditions. Abstract :